INTERNATIONAL CIVIL AVIATION LAW INSTRUMENTS AGAINST AIR TRANSPORT TERRORISM: AN ANALYSIS FROM THE ISLAMIC LAW PERSPECTIVE - Mustapha, Ismail Adua; Abolaji, Abdulraheem Taofeeq; Yusuph, Ismael Funsho (Jurnal Syariah, 2024)
Air transport terrorism is as old as the emergence of civil aviation itself. Illegal acts such as “air piracy” (aircraft hijacking); “aircraft destruction”; and kidnapping of passengers (“hostage-taking of passengers”) were popular ways of terrorizing air transport. To guide against the continuous perpetration of these heinous acts, the International Civil Aviation Organization member states wagged war through certain instruments such as definition, punishment, extradition of the offenders and the State with jurisdiction over the offence are stated in the anti-air terrorism conventions. Yet the various acts of terrorism persist to the extent that new emerging aviation terrorism activities are springing up either for political, economic or religious ideology. It is on this note that this paper analyses the instruments from the Islamic law perspective to the dynamism and development of Islamic law in its interaction with modern issues or practices such as civil aviation terrorism. The paper is doctrinal wherein qualitative legal research methodology is adopted. The primary and secondary sources of international civil aviation and Islamic law are analysed to achieve the aim and objectives of the paper. It is found that the act of air terrorism is rightly impermissible under Islamic law. It further finds that the definition of the offence under Islamic Law is wider than that of conventional law; jurisdiction is universal; punishment is more severe; and extradition is compulsory. The paper concludes that the act of terrorism in whatever form is tantamount to waging war against the principle of Maqasid al-Shari‘ah. The paper therefore recommends an urgent review of international civil aviation law instruments against air terrorism, particularly the provisions relating to punishment and jurisdiction, to be in line with Islamic law.